Regulatory Roles of Pectin Oligosaccharides on Immunoglobulin Production in Healthy Mice Mediated by Gut Microbiota. Issue 14 (19th June 2019) - Zhang, Shanshan; Hu, Haijuan; He, Wanying; Muhammad, Zafarullah; Wang, Lufeng; Liu, Fengxia; Pan, Siyi
Abstract : Scope: The prebiotic regulation of the gut microbiota is a promising strategy to induce protective humoral and mucosal immune responses. The potential immune‐improving effects of pectin oligosaccharides (POS) in healthy mice and the potential mechanism mediated by specific intestinal bacteria are investigated. Methods and results: POS is prepared using a hydrogen‐peroxide‐assisted degradation. Mice that consumed diets containing POS are tested for microbial community shifts, short‐chain fatty acids (SCFAs), and immunoglobulin (Ig) production using quantitative real‐time polymerase chain reaction, gas chromatography, and ELISA kits. Pearson's correlation analyses are performed between Ig production and specific intestinal bacteria or SCFAs. POS treatment significantly improves the growth of healthy mice. Moreover, 4‐week POS administration results in a profound change in intestinal microbial composition and a significantly higher fecal concentration of acetate, which leads to substantial increases of the levels of fecal secretory immunoglobulin A and serum IgG. Conclusions: The results suggest that the inclusion of POS in a diet can increase Ig production and optimize the composition of the gut microbiota. A significant correlation is observed between changes in Ig production and specific intestinal bacteria or acetate, providing insight into the mechanism of POS as a potential immune‐enhancing supplement. Abstract : The interplay of dietary pectin oligosaccharides (POS) supplementation, intestinal microbes, and immune factors is mainly focused on in this study. POS with complex chemical structure can increase immunoglobulin (Ig) production and optimize the composition of gut microbiota. Furthermore, significant correlations exist between changes in Ig production and specific bacteria, including Bacteroides, Bifidobacterium, and Lactobacillus, or their metabolite acetate.